First records of adult feeding in Megaloptera (Corydalidae, Corydalinae) from Mexico and their possible relationship with the increase in life span - Villagomez, Fernando; Contreras-Ramos, Atilano (Zootaxa, 2017)
Knowledge of the natural history of the order Megaloptera is incomplete. Immatures are long-lived and widely known for their role as aquatic predators (Contreras-Ramos 1998; Azevêdo & Hamada 2007), yet information on habits of the winged terrestrial adults is limited. Previously, it was thought that adults do not feed (Table 1), perhaps because of the relatively short life span of about one week to a month (Contreras-Ramos 1998, 1999; Hayashi 1993), as well as the inability of males of Corydalus Latreille, 1802 to feed due to their large mandibles. Tierno de Figueroa & Palomino (2002) analyzed the digestive tract of Sialis nigripes Pictet, 1865 in Spain, and found debris and a spermatophore in a female. Also, Contreras-Ramos (1999) recorded the acceptance of sugar water by adults of Platyneuromus soror (Hagen, 1861). However, consumption of solid organic matter in adult Megaloptera has not previously been recorded.